Pengaruh Ukuran Perusahaan terhadap Kinerja Keuangan Serta Implikasinya terhadap Nilai Perusahaan pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia - Wufron Wufron (Jurnal Wacana Ekonomi, 2017)
This study was conducted to determine the effect of company size on financial performance and its implications for firm value. Company size is proxied by total assets and total sales, financial performance is proxied by return on assets, while firm value is proxied by the value of tobin 's q. The theoretical basis used to support this research is signaling theory. This study uses a sample of manufacturing companies listed consistently on the Indonesia Stock Exchange (IDX) from 2010 to 2016. The data used is panel data. The data analysis technique used is path analysis. The results of the study explain that total assets have a negative and significant effect on financial performance, total sales have a positive and significant effect on financial performance, simultaneously total assets and total sales have a significant effect on financial performance, total assets have a negative and significant effect on firm value, total sales have a significant effect. positive and significant impact on firm value, financial performance has a positive and significant effect on firm value, simultaneously total assets, total sales and financial performance have a significant effect on firm value, financial performance can mediate the effect of total assets on firm value, and financial performance can mediate the effect total sales against firm value.